Evaluasi tata fasilitas objek wisata Pantai Matahari Terbit Desa Sanur Kaja Kota Denpasar - Eka Putra, I Putu Agus Juliarta; Sugianthara, Anak Agung Gede; Pradnyawathi, Ni Luh Made (Jurnal Arsitektur Lansekap, 2022)
Matahari Terbit Beach is one of the beach attractions in Denpasar City. This beach is equipped with various facilities to support visitor activities. But the facilities are not fully appropriate to supporting visitor activities, that is like the location of the facilities is not in accordance visitors activities, amount the facilities is still limited, here does it make the distribution uneven and still im complete, the condition of facilities much broken, and standart of facilities is not appropriate with applicable standards. This study aims to know the activities o visitors, to evaluate the available facilities, and to know the facilities that needto be added. The method used is a survey method with data collection technique through observation, interviews, questionnaires, documentation, and literature study. The result of research on visitors activities are water recreation, cycling, jogging, culinary, and relaxing. While there are some facilities that are not optimal on the location, quantity, condition, and not in appropriate with applicable standards facilities. That need to be added are security post, toilets, trash cans, stairs, hand washing stations, lighting, water recreation rentals, and souvenir sellers.